In vivo RNA-RNA recombination of coronavirus in mouse brain. - Keck, J G (1988)
RNA-RNA recombination between different strains of the murine coronavirus mouse hepatitis virus (MHV) occurs at a very high frequency in tissue culture. To demonstrate that RNA recombination may play a role in the evolution and pathogenesis of coronaviruses, we sought to determine whether MHV recombination could occur during replication in the animal host of the virus. By using two selectable markers, i.e., temperature sensitivity and monoclonal antibody neutralization, we isolated several recombinant viruses from the brains of mice infected with two different strains of MHV. The recombination frequency was very high, and recombination occurred at multiple sites on the viral RNA genome. This finding suggests that RNA-RNA recombination may play a significant role in natural evolution and neuropathogenesis of coronaviruses.